2010
DOI: 10.1007/978-3-642-12242-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Dynamic Trade Execution Strategies Using Grammatical Evolution

Abstract: Abstract. Although there is a plentiful literature on the use of evolutionary methodologies for the trading of financial assets, little attention has been paid to potential use of these methods for efficient trade execution. Trade execution is concerned with the actual mechanics of buying or selling the desired amount of a financial instrument of interest. Grammatical Evolution (GE) is an evolutionary automatic programming methodology which can be used to evolve rule sets. In this paper we use a GE algorithm t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…A novel approach was taken by [32,33] where grammatical evolution (GE) was used to evolve a dynamic trade execution strategy, with the resulting rule adapting to changing market conditions. Based on the finance literature analysing the relationship between order placement and the information content of limit order books, six order book metrics were selected as potential inputs for an execution strategy.…”
Section: Trading System Designmentioning
confidence: 99%
“…A novel approach was taken by [32,33] where grammatical evolution (GE) was used to evolve a dynamic trade execution strategy, with the resulting rule adapting to changing market conditions. Based on the finance literature analysing the relationship between order placement and the information content of limit order books, six order book metrics were selected as potential inputs for an execution strategy.…”
Section: Trading System Designmentioning
confidence: 99%
“…Noise agents (zero intelligence) Many researchers choose to use zero intelligence agents in their financial market simulations, for example in the models presented in [12,13,18,28]. There is a strong empirical evidence backing up such a widespread use of noise agents - [18] has shown that noise agents with parameters derived from empirical data can explain up to 96% of the variance of spreads and 76% of the diffusion rates.…”
Section: Human-like Agentsmentioning
confidence: 99%
“…There exist a number of noise agent variations. Relatively complicated strategies for noise traders are used in [12][13][14]. In these papers, the agents can submit Buy and Sell orders with equal probabilities, and can submit Limit and Market orders, or can cancel existing an limit order if it was not yet executed.…”
Section: Human-like Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work [6], GE has been used to evolve quality trade execution strategies which determine appropriate time to change limit orders to market orders. GE evolved strategies have been proved to outperform two benchmark strategies: simple market order strategy and simple limit order strategy.…”
Section: Introductionmentioning
confidence: 99%